2005
DOI: 10.1016/j.homp.2004.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoeconomic comparison between homeopathic and antibiotic treatment strategies in recurrent acute rhinopharyngitis in children

Abstract: Homeopathy may be a cost-effective alternative to antibiotics in the treatment of recurrent infantile rhinopharyngitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 3 publications
0
34
0
1
Order By: Relevance
“…24 Another comparative study investigated homeopathic and antibiotic treatment strategies in recurrent rhinopharyngitis in children aged 18 months to 4 years. 25 Episodes of rhinopharyngitis were reduced as were costs, and quality of life was better in the homeopathic care group. A sister study within the ALSPAC CAM study group showed no reduction in antibiotic use in homeopathic users.…”
Section: Discussionmentioning
confidence: 95%
“…24 Another comparative study investigated homeopathic and antibiotic treatment strategies in recurrent rhinopharyngitis in children aged 18 months to 4 years. 25 Episodes of rhinopharyngitis were reduced as were costs, and quality of life was better in the homeopathic care group. A sister study within the ALSPAC CAM study group showed no reduction in antibiotic use in homeopathic users.…”
Section: Discussionmentioning
confidence: 95%
“…Studies by Kooreman and Baars [31,32] reported that patients whose general practitioner has additional CAM training (including homeopathy) had lower health costs. Furthermore, homeopathic treatment of children with rhinopharyngitis was associated with lower direct medical costs and less sick leave time for their parents compared to standard antibiotic treatment [33]. Because of the rapidly growing health care cost in Western societies, cost-effective treatment options such as homeopathy may gain new (politic) interest.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Antibiotics are widely misused in patients with colds and URTI, with more than one third (35.7%) of all patients with this diagnosis receiving an antibiotic prescription. 3 This high level of use of prescription drugs such as antibiotics leads to suboptimal care, unnecessarily high health care costs, 4,5 and increasing levels of antibiotic resistance. 3,6 As part of their training, pharmacists are taught how to identify illnesses for which they can advise patients and deliver medication directly, over-the-counter (OTC), without the need for a medical prescription.…”
Section: What Is Already Known About This Subjectmentioning
confidence: 99%